Public perception towards Momogun term: a case study in N.31 Paginatan, Ranau / Barry Dausin and Treaccy Binos - Dausin, Barry; Binos, Treaccy (2017)
The purpose of this study is to investigate public perception towards Momogun term in N.31 Paginatan, Ranau. The objective of this study is to investigate public perception towards the "Momogun" term in N.31 Paginatan Ranau and to investigate either ethnic awareness, political orientation and cultural associations are associated with the study. These two objectives answered our research study in chapter 4 and further explained in chapter 5. This study was done by distributed questionnaires that involved 250 of respondents in N.31 Paginatan.